Semiconducting polymer nanomaterials as near-infrared photoactivatable protherapeutics for cancer - Li, Jingchao (2021)
Cancer therapy is routinely performed in the clinic to cure cancer and control its progression, wherein therapeutic agents are generally used. To reduce side effects, protherapeutic agents that can be activated by overexpressed cancer biomarkers are under development. However, these agents still face certain extent of off-target activation in normal tissues, stimulating the interest to design external-stimuli activatable protherapeutics. In this regard, photoactivatable protherapeutic agents have been utilized for cancer treatments. However, because of the intrinsic features of photolabile moieties, most photoactivatable protherapeutic agents only respond to ultraviolet-visible light, limiting their in vivo applications. Thus, protherapeutic agents that can be activated by near-infrared (NIR) light with minimal phototoxicity and increased tissue penetration are highly desired.In this Account, we summarize our semiconducting polymer nanomaterials (SPNs) as NIR photoactivatable protherapeutic agents for cancer treatment. SPNs are transformed from π-conjugated polymers that efficiently convert NIR light into heat or singlet oxygen (¹O₂). With photothermal and photodynamic properties, SPNs can be directly used as photomedicine or serve as light transducers to activate heat or ¹O₂₋ responsive protherapeutic agents.The heat-activatable SPN-based protherapeutic agents are developed by loading or conjugating of SPNs with therapeutic agents (e.g., agonist, gene, and enzyme). For instance, photothermally triggered release of agonists specifically activates certain protein ion channels on the cellular membrane, leading to ion overinflux induced mitochondria dysfunction and consequently apoptosis of cancer cells. Moreover, photothermal activation of temperature-sensitive bromelain can promote the in situ degradation of collagens (the major components of extracellular matrix), resulting in an improved accumulation of agents in tumor tissues and thus amplified therapeutic outcome.The¹O₂₋ activatable SPN-based protherapeutic agents are constructed through covalent conjugation of SPNs with caged therapeutic agents via hypoxia- or ¹O₂₋ cleavable linkers. Upon NIR photoirradiation, SPNs consume oxygen to generate ¹O₂, which leads to photodynamic therapy (PDT), and meanwhile breaks hypoxia- or ¹O₂₋ cleavable linkers for on-demand release and in situ activation of caged protherapeutic molecules (e.g., chemodrug, enzyme, and inhibitor). Such remote activation of SPN-based protherapeutic agents can be applied to induce DNA damage, ribonucleic acid degradation, inhibition of protein biosynthesis, or immune system activation in tumors of living animals. By synergizing PDT with NIR photoactivation of those biological actions, these protherapeutic agents effectively eliminate tumors and even fully inhibit tumor metastasis.This Account highlights the potential of SPNs for construction of versatile NIR photoactivatable protherapeutics to treat cancer at designated times and locations with high therapeutic outcome and precision.